PRINSIP PENULISAN KUESIONER PENELITIAN - Pujihastuti, Isti (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2010)
Questionnaire as an instrument of research is relatively often applied specifically to social research such as behavioral research, marketing research, human resources and others. This article discusses the importance of questionnaire for survey research. Statements or questions in the questionaire determine the success of the research related to the quality of the data, the primary data. The data quality depends on two things: the quality of the instrument and the quality of data collection techniques. Fundamentally (basic principles), the researcher should build the concept of variable. And the abstract concept called constructs. The concept of varying value will be variable. The next stage, these variables should be operationalized and it was measure based on dimensions (indicators. This is where the researchers tested actually associated with theoretical insights in terms of concept development. Technically the researcher need to note the signs of making the statements or questions, but the other required respondent’s understanding. Finally researchers need to control over the validity and reliability before the questionnaire distributed to the respondents.